2010
DOI: 10.1186/1471-2474-11-43
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Tai Chi in rheumatoid arthritis: a quantitative and qualitative study

Abstract: BackgroundRheumatoid arthritis (RA) is a chronic, inflammatory and systemic disease which affects the musculoskeletal system. Exercise programmes are reported to improve physical functioning in patients with RA. Tai Chi is a traditional Chinese martial art which combines slow and gentle movements with mental focus. The purpose of this study was to study in which way Tai Chi group exercise impacted on disease activity, physical function, health status and experience in RA patients, applying quantitative and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 42 publications
1
28
1
3
Order By: Relevance
“…Interventions based on mindfulness have repeatedly been shown to be effective in treating a variety of physical and mental disorders (Baer 2003;Grossman et al 2004;Hofmann et al 2010;Praissman 2008). The assumption that practicing Taiji might increase mindful awareness of one's bodily sensations is supported by findings reporting an increase of body awareness (Gyllensten et al 2010;Uhlig et al 2010) and kinetic sense (Jacobson et al 1997) due to Taiji practice. The influence of Taiji practice on self-attributed mindfulness in a broader context has been examined by Caldwell et al (2010).…”
Section: Introductionsupporting
confidence: 56%
“…Interventions based on mindfulness have repeatedly been shown to be effective in treating a variety of physical and mental disorders (Baer 2003;Grossman et al 2004;Hofmann et al 2010;Praissman 2008). The assumption that practicing Taiji might increase mindful awareness of one's bodily sensations is supported by findings reporting an increase of body awareness (Gyllensten et al 2010;Uhlig et al 2010) and kinetic sense (Jacobson et al 1997) due to Taiji practice. The influence of Taiji practice on self-attributed mindfulness in a broader context has been examined by Caldwell et al (2010).…”
Section: Introductionsupporting
confidence: 56%
“…An increased body awareness induced by regular Taiji practice has been reported in previous studies (Gyllensten et al, 2010;Uhlig et al, 2010) and is likely to enhance a resource activating embodiment. Maintaining resource activating embodiment in turn has been shown to reduce cortisol levels under resting conditions (Carney et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…The second study from the same group of investigators overcame the previous limitations, using a 12-week Tai Chi program for another 15 patients. They found that Tai Chi improved lower-limb muscle function and endurance at 12 weeks follow-up (Uhlig et al, 2010). A Cochrane review, examining the evidence from 4 clinical trials, suggested that Tai Chi does not exacerbate symptoms of rheumatoid arthritis and has some benefits on lower extremity range of motion for people with rheumatoid arthritis, in particular ankle range of motion .…”
Section: Scientific Evaluation Of Tai Chi For Rheumatoid Arthritismentioning
confidence: 99%